Transarterial chemoembolization combined with radiofrequency ablation for medium and large hepatocellular carcinoma: insufficient ablation is associated with intrahepatic distant metastasis and extrahepatic metastasis - Guo, Peng; Zheng, Junjun; Pi, Xingtao; Gao, Feng; Zhao, Yushan; Xie, Chunming; Cao, Wendong (Frontiers in Oncology, 2024)
Purpose: To compare the prognosis of complete and insufficient ablation of transarterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) in treating medium and large hepatocellular carcinoma (HCC) and to explore the differences in recurrence patterns between the two groups.Patients and Methods: Patients´medical records and imaging data of patients with confirmed HCC from January 2014 to January 2022 were collected. These patients were divided into 2 groups: complete ablation (n=172) and insufficient ablation (n=171). Overall survival (OS) and progression-free survival (PFS) were estimated by the Kaplan-Meier curve and the log-rank test was used to compared. Fisher's exact test was used to compare recurrence patterns between the two groups.Results: The median OS time was 72.8 months (95%CI:69.5-76.1) and 62.0 months (95%CI: 55.3-68.7) in the complete and insufficient ablation groups, respectively. The median PFS time in the complete ablation group was 67.8 months (95% CI: 65.2-70.4) and 38.6 months (95%CI: 29.8-47.4) in the insufficient ablation group. The OS and PFS rates of the complete ablation group were significantly better than those of the insufficient ablation group (P<0.001). In the complete ablation group, 25(41%) patients experienced local tumor progression(LTP), 36(59%) experienced intrahepatic distant progresssion(IDP), and 0(0%) experienced extrahepatic progression (EP). In the insufficient ablation group, 51 (32.1%) patients experienced LTP, 96 (60.4%) experienced IDP, and 12 (7.5%) experienced EP. The progression patterns of the two groups were statistically significant (P=0.039).Conclusion: Insufficient ablation indicates a poor survival outcome of TACE combined with RFA for medium and large HCC and can promote intrahepatic distant and extrahepatic metastasis.